A Novel Protein Glycan Biomarker and Future Cardiovascular Disease Events. Issue 5 (23rd September 2014) - Akinkuolie, Akintunde O.; Buring, Julie E.; Ridker, Paul M; Mora, Samia
Abstract : Background: Glycosylated proteins partake in multiple cellular processes including inflammation. We hypothesized that GlycA, a novel biomarker of protein glycan N ‐acetyl groups, is related to incident cardiovascular disease (CVD), and we compared it with high‐sensitivity C‐reactive protein (hsCRP). Methods and Results: In 27 491 initially healthy women, baseline GlycA was quantified by nuclear magnetic resonance spectroscopy and hsCRP by an immunoturbidimetric assay. During median follow‐up of 17.2 years, 1648 incident CVD events occurred (myocardial infarction, ischemic stroke, coronary revascularization, and CVD death). GlycA and hsCRP were moderately correlated (Spearman r =0.61, P <0.0001). In Cox regression models that included age, ethnicity, smoking, blood pressure, medications, menopausal status, body mass index, and diabetes, hazard ratios for CVD across quartiles 1 to 4 of GlycA were 1.00, 1.10 (95% CI, 0.92 to 1.30), 1.34 (95% CI, 1.13 to 1.58), and 1.64 (95% CI, 1.39 to 1.93), similar to hsCRP, for which hazard ratios were 1.00, 1.18 (95% CI, 0.99 to 1.41), 1.35 (95% CI, 1.14 to 1.61), and 1.75 (95% CI, 1.47 to 2.09) (both P trend <0.0001). Associations were attenuated after additionally adjusting for lipids: the hazard ratio of quartile 4 versus 1 for GlycA was 1.23 (95% CI, 1.04 to 1.46; P trend =0.002) and for hsCRP was 1.44 (95% CI, 1.20 to 1.72; P trend <0.0001). Further adjustment for the other biomarker resulted in a hazard ratio of quartile 4 versus 1 for GlycA of 1.03 (95% CI, 0.85 to 1.24; P trend =0.41) and for hsCRP of 1.29 (95% CI, 1.06 to 1.56; P trend =0.001). Conclusions: In this prospective study of initially healthy women, baseline GlycA was associated with incident CVD, consistent with a possible role for protein glycans in inflammation and CVD. Clinical Trial Registration: URL: http//clinicaltrials.gov/. Unique identifier NCT00000479.